Re-evaluating ‘Denmark’s Stonehenge’ - Lone Claudi-Hansen; Arne Anderson Stamnes (Danish Journal of Archaeology, 2023)
In 1965, an aerial photograph from eastern Denmark revealed three concentric circles surrounding a large hill. In the following years, the National Museum conducted two small excavations, which seemed to confirm that these circular marks reflected concentric circles of features and large stone holes, but the reports were never completed. The site was later classified as a ‘stone- or woodhenge’. In this paper we assess the interpretation of the aerial photograph and archaeological features around the prominent hill based on a re-excavation and ground-penetrating radar survey of a part of the site. While no circular structures can be identified, we argue that clusters of fire pits at the side of the steep hill represent communal activities from the Bronze Age, which combines the transformative elements of fire with the distinctive landscape of the large hill and the surrounding burial monuments. The site thereby serves as an example that links prominent hilltops surrounded by burial mounds, with the event of establishing fire pits in clusters.